Dynamic sustainability performance during urbanization process between BRICS countries. (February 2017) - Shen, Liyin; Shuai, Chenyang; Jiao, Liudan; Tan, Yongtao; Song, Xiangnan
Abstract: Brazil, Russia, India, China and South Africa (BRICS) as the emerging leading powers in the world have great influence on the world development. Urbanization process has been a significant engine for development in these countries, which has important effect on the sustainable development globally. However, rapid urbanization has induced various problems, such as air pollution, traffic congestion, habitat destruction, and loss of arable land. These problems present the threats to the sustainable development of urbanization in these countries. This paper presents an evaluation on the dynamic sustainability performance during urbanization process in these countries by applying an elastic coefficient method and a new-type McKinsey matrix. The data used for analysis are collected from World Bank database for the period of 1990–2011. The findings from this study suggest that during the surveyed period the Brazil, Russia and India have been engaging a sustainable urbanization practice, whilst the urbanization processes in China and South Africa are unsustainable. The study provides valuable reference in searching for solutions to further promote sustainable urbanization practice globally.